French Multicentric Evaluation of Recombinant Tissue Factor (Recombiplastin) for Determination of Prothrombin Time - Roussi, J; Drouet, L; Samama, M; Sié, P; Bal, C; Boudaoud, L; Cazenave, J P; Denninger, M H; Droule, Ch; Horellou, M H; Levy, G; Mazoyer, E; Sampol, J; Schved, J F; Vergnes, C (Thrombosis and Haemostasis, 1994)
Recombiplastin, a recombinant a human tissue factor, elaborated by Ortho Diagnostic Systems, produced by Baculovirus and relipidated with highly purified phospholipids, was tested as a new reagent for determining prothrombin time (PT) in a French multicentric study. Its intralaboratory- performances, including sensitivity, repeatability, reproducibility and stability, were explored to establish whether its use would reduce the interlaboratory dispersion of PT values, and therefore improve the standardization of oral anticoagulant treatment.The 9 university hospital hematology laboratories involved in this study used the same type of instrument (KC 10). For 10 consecutive days, they determined PTS on a normal plasma pool, plasma dilutions of 1/2, 1/3 and 1/8, 3 identical lyophilized calibrated plasmas, as well as plasmas from 20 normal subjects, 50 patients on oral anticoagulant therapy with Recombiplastin which has an International Sensitivity Index (ISI) of 1, and 2 commercial thromboplastin extracts (ISI #1 or 2). In the patients on anticoagulants, factors VII, X and V were measured when results were conflicting.The intra and interlaboratory reproducibilities of Recombiplastin, calculated on the basis of either PTS expressed in seconds, or of the International Normalized Ratio (INR), were good, with coefficients of variation (CV) similar to those observed with the 5 other reagents used by the different laboratories (2% <CV <8%).The stability of Recombiplastin was excellent, with no variation in PT after 72 h of incubation at 37° C.A normal PT of 12 s was obtained with Recombiplastin, similar to the values found for the reagents with ISI #2. In the patients on anticoagulants, Recombiplastin gave the longest coagulation times (PTRecombipiastin = 64.2 s vs PTNeoPlastin = 32.8 s, and PTThromborel = 54.4 s). These results suggest that Recombiplastin is highly sensitive to the changes in coagulation induced by anticoagulants. Recombiplastin was more sensitive to factor VII deficiency than any of the other reagents, even those with ISI #1.The coefficients of correlation between the INRS calculated on the basis of the PTS obtained with Recombiplastin and the INRS based on the PTS for other thromboplastins, were satisfactory (0.85 <R <0.95) but a breakpoint in the slope of the regression curves was observed when INR >4. This observation requires further investigation, particularly in connection with the exact ISI values for Recombiplastin and the other thromboplastins used in this study.In conclusion, Recombiplastin is stable and sensitive and gives accurate reproducible results. However, the behavior of Recombiplastin is slightly different from that of the commercial reagents whether their ISI is 1 or 2, and its use did not reduce the interlaboratory dispersion of PT values.